Electric vehicles standards, charging infrastructure, and impact on grid integration: A technological review. (March 2020) - Das, H.S.; Rahman, M.M.; Li, S.; Tan, C.W.
Abstract: Transportation electrification is one of the main research areas for the past decade. Electric vehicles (EVs) are taking over the market share of conventional internal combustion engine vehicles. The increasing popularity of EVs results in higher number of charging stations, which have significant effects on the electricity grid. Different charging strat2egies, as well as grid integration methods, are being developed to minimize the adverse effects of EV charging and to strengthen the benefits of EV grid integration. In this paper, a comprehensive review of the current situation of the EV market, standards, charging infrastructure, and the impact of EV charging on the grid is presented. The paper introduces the current EV status, and provides a comprehensive review on important international EV charging and grid interconnection standards. Different infrastructure configurations in terms of control and communication architectures for EV charging are studied and evaluated. The electric power market is studied by considering the participation roles of EV aggregators and individual EV owners, and different optimization and game based algorithms for EV grid integration management are reviewed. The paper specially presents an evaluation on how the future EV development, such as connected vehicles, autonomous driving, and shared mobility, would affect EV grid integration as well as the development of the power grid moves toward future energy Internet and how EVs would affect and benefit the development of the future energy Internet. Finally, the challenges and suggestions for the future development of the EV charging and grid integration infrastructure are evaluated and summarized. Highlights: An overview of the current situation and future development trend of the EV market. A detailed review of standards associated with EVs and EV grid integration. An in-depth evaluation of EV charging and grid integration infrastructure. A summary of limitations and suggestions on EV charging and grid integration. An assessment of the importance and role of EVs in the future energy internet with the development of automobile industry.